MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATEMATIKA - Elsa Radiati (Jurnal Edukasi dan Penelitian Matematika, 2018)
Understanding of mathematical concepts was one of a bilities that must be known by students. Based on the observation, understanding of mathematical concepts and learning activities of students in grade VII SMPN 12 Padang were still low and needed to be improved again, so that students could understand concepts well. Purpose of this study were to describe learning activities of students and to know whether student’s understanding ofmathematical conceptswho learned by using cooperative learning modelTTW type was better than those who learned by using conventional learning in grade VII SMPN 12 Padang. This study was a combination between descriptive study and quasi-experimental with static group design. Sampling was done by simple random sampling. Based on result of data analysis, it can be concluded that student’s understanding of mathematical concepts using cooperative learning model TTW type is better than those using conventional learning.Keywords –mathematical concepts, learning activities,think talk write.